Pasteurisation and the control of milkborne infection in Britain. Issue 6493 (17th August 1985) - Sharp, J C; Paterson, G M; Barrett, N J
Abstract : Infections carried in milk, particularly salmonellosis and campylobacter enteritis, have continued to feature in Great Britain in recent years. Less commonly reported infections included an outbreak in 1984 in England due to Streptococcus zooepidemicus, in which 12 people, eight of whom died, were admitted to hospital. The implementation of legislation in 1983 requiring heat treatment of cows' milk for sale to the public reduced the incidence of milkborne infection in Scotland compared with previous years and compared with England and Wales, where, without legislative control, outbreaks continue to occur. Until compulsory pasteurisation is introduced throughout Britain and dairy farming communities can be persuaded to drink only heat treated milk outbreaks of milkborne infection will continue.